OPTIMIZATION OF PHYSICAL, MECHANICAL AND DEGRADATION PROPERTIES FOR BIODEGRADABLE ANTI-ADHESIVE MEMBRANES - M. V. Nasonova; Yu. I. Hodyrevskaya; A. I. Nemoykina; M. Yu. Mikhaylenko; Yu. A. Kudryavtseva (Вестник Кемеровского государственного университета, 2015)
Biodegradation rate and tensile strength are essential for membranes, applied to prevent post-surgical adhesion formation. The study is aimed at evaluating biodegradation rate, physical and mechanical properties of the membranes made from biodegradable polymer composites in vitro, namely polyhydroxybutyrate / oxovalerate (PGBV), polylactide (PLA), and polylactide-co-glycolide (PLGA). PLGA copolymers, having a polylactide: glycolide ratio in the proportion of 70:30 and 60:40, reported the highest biodegradation rate, moreover, the addition of PGBV to this polymer composite may increase the bioresorption rate of the latter by1.2 – 1.3 times. Thus, the physical and mechanical testing findings have shown that the addition of PLGA to PGBV results in improved properties of the studied samples – PLGA added to the polymer composite in the proportion 60:40 increased its strength by 27.5 %, and its elastic properties by 70 % compared to PGBV. The obtained results demonstrated that the adjustment of the bioresorbable polymer formulation for anti-adhesive membranes may regulate biodegradation rate, physical and mechanical properties.